Global Tends in the Corporate Reporting Development - E. B. Abdalova; S. N. Karelskaia (Учёт. Анализ. Аудит)
The paper covers the disclosure of information on company’s climate risks in corporate reporting, which is the urgent agenda. It was found that 16 of International Financial Reporting Standards (IFRS) provide the opportunity for disclosing of such climate risks. However, they contain significant restrictions regarding the presentation of forecasting information. The analysis revealed the current stages of corporate reporting development under the influence of the relevant disclosure of climate risks by companies. The research data source includes the publications and statements available on the official website of the IFRS Foundation**. The research results can be useful for professional international organisations and Russian state bodies engaged in the development of financial and non-financial reporting standards, concerned users, as well as economic entities that prepare corporate reporting.